Suspected Case of Drug-Induced Acute Respiratory Distress Syndrome following Trimethoprim-Sulfamethoxazole Treatment - Natterer, Julia; Rizzati, Frida; Perez, Marie-Hélène; Longchamp, David; Amiet, Vivianne; DeHalleux, Quentin; Dao, Kim; Ferry, Thomas (Journal of Pediatric Intensive Care, 2020)
In this article, we reported the case of a child patient who was admitted to our PICU for severe acute respiratory distress syndrome (ARDS) while being treated with trimethoprim-sulfamethoxazole (TMP-SMX) for osteomyelitis. Based on the timing of exposure, lack of alternative explanations, and clinical course similar to previously described cases, we suspect that TMP-SMX may have triggered ARDS. Despite meeting criteria for extracorporeal membrane oxygenation cannulation, conservative management and lung recruitment with high-frequency percussive ventilation could avoid the latter.
Keywords: acute respiratory distress syndrome; trimethoprim; percussive ventilation